Opioids After Surgery in the United States Versus the Rest of the World: The International Patterns of Opioid Prescribing (iPOP) Multicenter Study. Issue 6 (December 2020) - Kaafarani, Haytham M. A.; Han, Kelsey; El Moheb, Mohamad; Kongkaewpaisan, Napaporn; Jia, Zhenyi; El Hechi, Majed W.; van Wijck, Suzanne; Breen, Kerry; Eid, Ahmed; Rodriguez, Gabriel; Kongwibulwut, Manasnun; Nordestgaard, Ask T.; et al.
Abstract : Objective: The International Patterns of Opioid Prescribing study compares postoperative opioid prescribing patterns in the United States (US) versus the rest of the world. Summary of Background Data: The US is in the middle of an unprecedented opioid epidemic. Diversion of unused opioids contributes to the opioid epidemic. Methods: Patients ≥16 years old undergoing appendectomy, cholecystectomy, or inguinal hernia repair in 14 hospitals from 8 countries during a 6-month period were included. Medical records were systematically reviewed to identify: (1) preoperative, intraoperative, and postoperative characteristics, (2) opioid intake within 3 months preoperatively, (3) opioid prescription upon discharge, and (4) opioid refills within 3 months postoperatively. The median/range and mean/standard deviation of number of pills and OME were compared between the US and non-US patients. Results: A total of 4690 patients were included. The mean age was 49 years, 47% were female, and 4% had opioid use history. Ninety-one percent of US patients were prescribed opioids, compared to 5% of non-US patients ( P < 0.001). The median number of opioid pills and OME prescribed were 20 (0–135) and 150 (0–1680) mg for US versus 0 (0–50) and 0 (0–600) mg for non-US patients, respectively (both P < 0.001). The mean number of opioid pills and OME prescribed were 23.1 ± 13.9 in US and 183.5 ± 133.7 mg versus 0.8 ± 3.9 and 4.6 ± 27.7 mg in non-US patients, respectively (both P < 0.001). Opioid refill rates were 4.7% for US and 1.0% non-US patients ( P < 0.001). Conclusions: US physicians prescribe alarmingly high amounts of opioid medications postoperatively. Further efforts should focus on limiting opioid prescribing and emphasize non-opioid alternatives in the US. Abstract : Supplemental Digital Content is available in the text